Cenozoic tectonic evolution of the Bohai Bay Basin and its coupling relationship with Pacific Plate subduction. (1st September 2016) - Liang, Jintong; Wang, Hongliang; Bai, Ying; Ji, Xinyuan; Duo, Xuemei
Highlights: The migration of depression centers in the Bohai Bay Basin is well-regulated. Characteristics of BBB tectonic evolution changed periodically. The BBB tectonic evolution is affected by the Pacific Plate subduction. Abstract: The Bohai Bay Basin is a Mesozoic–Cenozoic rift basin in eastern China. Based mainly on a balanced-section analysis, this study compares the spatio-temporal differences of tectonic evolution in relation to strike-slip faults among different depressions within the basin. In combination with the analysis of subsidence characteristics, the study also attempts to clarify the Cenozoic tectonic evolution of the basin and its coupling relationship with the subduction of the Pacific Plate. It was found that: (1) the strike-slip faults were activated generally from south to north and from west to east during the Cenozoic; (2) there is a negative correlation between the intensity of tectonic activity in the Bohai Bay Basin and subduction rate of the Pacific Plate; and (3) the migration direction of the basin depocenters is consistent with the direction of Pacific Plate subduction.